Sputum smear non-conversion among adult persons with bacteriologically confirmed pulmonary tuberculosis in rural eastern Uganda - Izudi, Jonathan (J Clin Tuberc Other Mycobact Dis, 2020)
RATIONALE: Failure to convert sputum at two months of treatment among persons with bacteriologically confirmed pulmonary tuberculosis (BC-PTB) indicates poor response to treatment but data are limited on its assessment. OBJECTIVE: We determined the frequency and factors associated with sputum smear non-conversion at two months among persons with BC-PTB in eastern Uganda. METHODS: We abstracted data of adult persons with BC-PTB, from routinely available records from TB registers at 10 clinics in eastern Uganda. We determined factors that are independently associated with sputum smear non-conversion using logistic regression analysis. We expressed the results as odds ratio (OR) with 95% confidence interval (CI). MEASUREMENTS AND MAIN RESULTS: Of 516 persons with BC-PTB, 81 (15.7%) did not achieve sputum smear conversion at two months of TB treatment. Higher Mycobacteria tuberculosis (MTB) load and treatment at a private-not-for-profit (PNFP) facility compared to government health facility were significantly associated with sputum smear non-conversion. A one unit (+1) increase in MTB load based on ZN stain counts was associated with a 48% increase in the odds of sputum smear non-conversion with adjusted odds ratio (AOR), 1.48 (95% CI, 1.02–2.18). TB treatment at private-not-for-profit health facility was associated with a two-fold increase in the odds of sputum smear non-conversion (AOR, 2.03; 95% CI, 1.01–3.92). CONCLUSIONS: Our study shows that sputum smear non-conversion is common at two months of treatment in this population. It is more likely among patients with higher baseline MTB load and those treated at PNFP facilities. Strategies targeting patients with these risk factors are needed to enhance sputum smear conversion.